An Intertypic Herpes Simplex Virus Helicase-Primase Complex Associated with a Defect in Neurovirulence Has Reduced Primase Activity - Barrera, I. (American Society for Microbiology, 1998)
R13-1 is an intertypic recombinant virus in which the left-hand 18% of the herpes simplex virus type 1 (HSV-1) genome is replaced by homologous sequences from HSV-2. R13-1 is nonneurovirulent and defective in DNA replication in neurons. The defect was localized to the UL5 open reading frame by using marker rescue analysis (D. C. Bloom and J. G. Stevens, J. Virol. 68:3761–3772, 1994). To provide conclusive evidence that UL5 is the only HSV-2 gene involved in the restricted replication phenotype of R13-1, we have characterized the phenotype of a recombinant virus (IB1) in which only the UL5 gene of HSV-1 was replaced by HSV-2 UL5. Data from 50% lethal dose determinations and the in vivo yields of virus suggested that IB1 has the same phenotypic characteristics as R13-1. UL5 is the helicase component of a complex with helicase and primase activities. All three subunits of this complex (UL5, UL8, and UL52) are required for viral DNA replication in all cell types. The intertypic complex HSV-2 UL5–HSV-1 UL8–HSV-1 UL52 was purified and biochemically characterized. The primase activity of the intertypic complex was 10-fold lower than that of HSV-1 UL5–HSV-1 UL8–HSV-1 UL52. The ATPase activity was comparable to that of the HSV-1 enzyme complex, and although the helicase activity was threefold lower, this did not interfere with the synthesis of leading strands by the HSV polymerase. One explanation for these findings is that the interactions between the subunits of the helicase-primase intertypic complex that are important for the full function of each subunit are inappropriate or weak.